Pelatihan Dan Pendampingan Agripreneur Dalam Mendorong Keberhasilan Usaha Pertanian - Sutrisno Sutrisno; Asruni Azis; Dasmaniar Dasmaniar; Sangkala Irwan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT The agricultural sector plays an important role in improving the community economy but still faces various challenges such as limited entrepreneurial skills among farmers, lack of business innovation, and minimal use of marketing technology. This community service program aimed to improve community agripreneur capabilities through agricultural business training and mentoring. The implementation methods included participant needs identification, agricultural entrepreneurship training, agricultural product marketing education, business mentoring, and evaluation using pre-test and post-test methods. The activity involved 30 participants consisting of farmers and young farmers. The results showed an increase in participants’ knowledge regarding agricultural business management, digital marketing, and agricultural product management, with the average pre-test score increasing from 55 to 87 in the post-test. In addition, participants began implementing more effective marketing and business management strategies. This program proved effective in improving community motivation and skills in developing agripreneur-based agricultural businesses. Keywords: Agripreneur, Agricultural Business, Community Empowerment, Training, Mentoring ABSTRAK Sektor pertanian memiliki peran penting dalam meningkatkan perekonomian masyarakat, namun masih menghadapi berbagai permasalahan seperti rendahnya kemampuan kewirausahaan petani, keterbatasan inovasi usaha, dan kurangnya pemanfaatan teknologi pemasaran. Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan kemampuan agripreneur masyarakat melalui pelatihan dan pendampingan usaha pertanian. Metode pelaksanaan meliputi identifikasi kebutuhan peserta, pelatihan kewirausahaan pertanian, edukasi pemasaran hasil pertanian, pendampingan usaha, serta evaluasi kegiatan menggunakan pre-test dan post-test. Kegiatan diikuti oleh 30 peserta yang terdiri dari petani dan pemuda tani. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan peserta mengenai manajemen usaha pertanian, pemasaran digital, dan pengelolaan hasil pertanian dengan rata-rata nilai pre-test sebesar 55 meningkat menjadi 87 pada post-test. Selain itu, peserta mulai mampu menerapkan strategi pemasaran dan pengelolaan usaha secara lebih efektif. Program ini terbukti mampu meningkatkan motivasi dan keterampilan masyarakat dalam mengembangkan usaha pertanian berbasis agripreneur. Kata Kunci: Agripreneur, Usaha Pertanian, Pemberdayaan Masyarakat, Pelatihan, Pendampingan